2003
DOI: 10.1074/jbc.m300781200
|View full text |Cite
|
Sign up to set email alerts
|

The Treponema pallidum tro Operon Encodes a Multiple Metal Transporter, a Zinc-dependent Transcriptional Repressor, and a Semi-autonomously Expressed Phosphoglycerate Mutase

Abstract: The Treponema pallidum tro operon encodes an ABC transporter (TroABCD), a transcriptional repressor (TroR), and the essential glycolytic enzyme phosphoglycerate mutase (Gpm). The apparently discordant observations that the solute binding protein (TroA) binds Zn 2؉ , whereas DNA binding by TroR in vitro is Mn 2؉ -dependent, have generated uncertainty regarding the identities of the ligand(s) and co-repressor(s) of the permease. Moreover, this operonic structure suggests that Gpm expression, and hence glycolysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(114 citation statements)
references
References 61 publications
5
109
0
Order By: Relevance
“…Although the presence of His at position 207 in Tpa-TroA suggests Zn 2+ specificity, ligation by Asp279 and the absence of the His-rich loop indicate Mn 2+ specificity. Thus, Tpa-TroA might transport both Zn 2+ and Mn 2+ , which would be consistent with its similar binding affinities for the two metal ions [19]. It may be that nature has built flexibility into these proteins to handle different metal ions in response to availability and need.…”
Section: Metal Specificitymentioning
confidence: 53%
See 3 more Smart Citations
“…Although the presence of His at position 207 in Tpa-TroA suggests Zn 2+ specificity, ligation by Asp279 and the absence of the His-rich loop indicate Mn 2+ specificity. Thus, Tpa-TroA might transport both Zn 2+ and Mn 2+ , which would be consistent with its similar binding affinities for the two metal ions [19]. It may be that nature has built flexibility into these proteins to handle different metal ions in response to availability and need.…”
Section: Metal Specificitymentioning
confidence: 53%
“…The structural and biochemical data presented here combined with previous reports [7,10,11,15,19] provide insight into the mechanism of metal acquisition and transport by Eco-ZnuA. The binding of Zn 2+ in the main metal binding site of apoZnuA probably results in local conformational changes in the loop that houses ligands Glu59 and His60 (Fig.…”
Section: Mechanistic Implicationsmentioning
confidence: 76%
See 2 more Smart Citations
“…Intriguingly, the deduced sequence of this ϳ170-aa region of CT069 shares homology with T. pallidum TroR ( Fig. 2A), an aporepressor that regulates transcription of the tro operon in the presence of a corepressor, Zn 2ϩ or Mn 2ϩ (20,34). CLUSTAL W alignment revealed that the region from aa 1 to 313 of CT069 has 23.0% identity and 45.7% similarity with T. pallidum TroC, whereas aa 286 to 451 of CT069 have 21.8% identity and 28.2% similarity with T. pallidum TroR (Fig.…”
Section: Resultsmentioning
confidence: 99%